2010
DOI: 10.5194/angeo-28-1249-2010
|View full text |Cite
|
Sign up to set email alerts
|

On the correlation between Broad-Band ELF wave power and ion fluxes in the cusp

Abstract: Abstract. We present a study of Broad-Band Extremely Low Frequency (BB-ELF) electric fields in the mid-altitude (4-6 Earth radii) cusp during periods of southward interplanetary magnetic field, using data from the Cluster spacecraft. Magnetospheric boundary layers are identified and classified according to particle precipitation characteristics. We find that the BB-ELF is contained within the cusp ion precipitation region, and its onset is closely co-located with the equatorward edge of the cusp ion dispersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Numerous Cluster studies have shown that the low-frequency wave power correlates with the fluxes of the magnetosheath-like ions and electrons seen in the cusp (e.g., Duan et al, 2006;Grison et al, 2005;Jacobsen & Moen, 2010;Keith et al, 2005). Jacobsen and Moen (2010) pointed out that there is a greater degree of correlation between BBELF wave power and total fluxes in comparison with only field-aligned ion fluxes, suggesting that BBELF wave generation is independent of ion beam direction and therefore must be local.…”
Section: Low Frequency Wavesmentioning
confidence: 99%
“…Numerous Cluster studies have shown that the low-frequency wave power correlates with the fluxes of the magnetosheath-like ions and electrons seen in the cusp (e.g., Duan et al, 2006;Grison et al, 2005;Jacobsen & Moen, 2010;Keith et al, 2005). Jacobsen and Moen (2010) pointed out that there is a greater degree of correlation between BBELF wave power and total fluxes in comparison with only field-aligned ion fluxes, suggesting that BBELF wave generation is independent of ion beam direction and therefore must be local.…”
Section: Low Frequency Wavesmentioning
confidence: 99%
“…Broadband extremely low frequency (BBELF) fields are observed from the upper ionosphere to several R E out. BBELF refers to electromagnetic fluctuations from 3 to 5 kHz down to quasi-static levels Ivchenko and Marklund, 2001;Lorentzen et al, 2007;Jacobsen and Moen, 2010]. Lund et al [2000] mapped the occurrence rates of BBELF waves down to 1000 km altitude.…”
Section: Ion Upflow and Outflowmentioning
confidence: 99%
“…The first step is the initial acceleration of bulk ion upflow events driven by ion heating and ambipolar diffusion as observed by incoherent scatter radars (ISRs) [ Wahlund et al ., ; Ogawa et al ., , , ; Buchert et al ., ; Skjæveland et al ., ], sounding rockets [ Arnoldy et al ., ; Lynch et al ., ; Frederick‐Frost et al ., ], and satellites in polar low Earth orbit in the F region ionosphere [ Coley et al ., ; Ogawa et al ., ; Lühr et al ., ; Chaston et al ., ; Lorentzen et al ., ; Sadler et al ., ]. The second step is that upflow events that have reached sufficiently high altitudes are exposed to wave energies available in the topside ionosphere/magnetosphere which drive nonthermal transverse acceleration of oxygen [ André and Yau , ; Strangeway et al ., ; Chaston et al ., ; Jacobsen and Moen , ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 The energization has been associated with enhanced broadband extra low frequency wave power in the frequency range between 1 Hz and 1 kHz (e.g., Refs. 36,42,and 45). However, the free energy source for the wave growth and the identification of the wave modes responsible for ion heating are still open issues.…”
Section: Introductionmentioning
confidence: 99%